Private military contractors gains in containing Boko Haram in Nigeria - Mkandla, Thando Ian (My University, 2017)
The growing role of Private Military Companies (P.M.C) has led to a magnitude of security concerns internationally. Due to their past reputation, P.M.Cs have been demonised by the international community in the form of scholars as well as journalists, as their personnel have been misunderstood for mercenaries (De Nevers 2009). It is therefore important to clarify the difference between contractors and mercenaries. However due to the growth of different actors and security threats, Private Military Companies have emerged as an effective alternative solution in engaging non-traditional threats in the international arena, a role states have increasingly failed in. Private Military Companies have become more successful in applying counterinsurgency tactics due to their structural setup, skills and expertise as well as technological advancement and understanding of warfare. This has led to an increase in reliance from states including the United States, Angola, and more recently Nigeria. Through the examination of the Nigerian case study, the thesis paper aims to understand how the P.M.C (S.T.T.E.P) was able to apply its COIN tactics effectively in combating Boko Haram. It is important to examine the Nigerian case study as P.M.C success could possibly be used to combat the proliferation of terrorist manoeuvres such as Al-Shabaab. The Nigerian case is also important as it displays how S.T.T.E.P working together with the N.D.F could strengthen their COIN campaign against Boko Haram.
Submitted in partial fulfilment of the requirements for the degree of Master of Arts of International Relations in the Faculty of Humanities Department of International Relations, Johannesburg 2017
Keywords: Boko Haram; Terrorist organizations--Nigeria; Private military companies--Nigeria